Investigating the Effect of Kaizen Management on Industrial Performance at Kathmandu Valley: Empirical Evidence of Japanese Management Theory - Kutu, Nischal; Chalise, Mahananda; Danuwar, Ranjana Kumari (Quest Journal of Management and Social Sciences, 2024)
Background: Kaizen, originating from Miyazaki et al. (1986), emphasizes efficient work approaches, impacting global businesses. Despite its widespread adoption, Nepal faces queries regarding its efficacy and implementation challenges. Objective: This study examines the effect of Kaizen Management on Industrial Performance at Kathmandu Valley – one of the core business cities of South Asia as well as challenges of Kaizen Management by providing the managerial solution for effective Kaizen Management. Methods: Following the Japanese Management Theory (Theory Z), an explanatory research design is employed to identify causal relationships between variables in the study of Kaizen management. Based in the Kathmandu Valley, managers from 158 industries (35 from Bhaktapur, 62 from the Balaju Industrial Estate, and 61 from the Patan Industrial Estate) were selected using probability sampling techniques, and primary data were collected via survey methods using structured questionnaires. Results: Employee Skills & Efforts, Working Area Impact, and Follow-up Activities all have a significant impact on how Kaizen management is implemented. This finding provides theoretical support for Japanese Management Theory. According to the results, Kaizen management is a new idea that has to be given greater consideration in Nepalese industrial estates. Conclusion: Organizational rules and procedures need to be changed and amended more so that staff members, supervisors, and organizations may make significant strides in implementing Kaizen Management across industries in Kathmandu valley. Keywords: Kaizen Management, Industrial Estate, Structural Equation Modelling, Nepal Paper Type: Research Paper JEL Classification: J53, M11, M12, O32, G32